ANALISIS KEMAMPUAN MATEMATIKA MAHASISWA CALON GURU MATEMATIKA DALAM MENYELESAIKAN MASALAH MATEMATIKA - Muhammad Samad Rumalean (Science Map Journal, 2022)
The purpose of this study was to determine the level of mathematical ability of prospective mathematics teacher students in solving SBMPTN math problems. This research was conducted at the Pattimura University Mathematics Education Study Program, Ambon. The subjects in this study were 19 prospective mathematics teacher students in the 3rd semester of 2017. The instrument used in this study was the Mathematical Ability Test (TKM) to classify the level of the mathematical knowledge of the research subjects with the following steps: 1) preparing instruments; 2) determining research subjects 3) carrying out research 4) performing data analysis of data collection; 5) formulate research results and discussion. The readability test results stated that the instrument was suitable for use in research. The empirical validity results show that it is 70% valid and has high reliability. The results showed that: 1) 5.26% of student math teacher candidates had a high level of math skills, 2) 10.53% of student teacher candidates had moderate math ability levels, and 3) 81.21% of student math teacher candidates had low math ability levels